Three new records of Cladocera (Crustacea: Branchiopoda) for the State of Maranhão, Northeastern Brazil - Santos, Arielly De S.; Andrade, Daniel Da S.; Sousa, Francisco Diogo Rocha; Mugnai, Riccardo (Zootaxa, 2023)
Brazilian biodiversity is still poorly studied, especially in the northeast region of Brazil. In the state of Maranhão, the rich fauna is still under-explored in relation to the Cladocera, and this geographic area covers four biomes, which makes it an important field of research on the Cladocera community. In this work, the record of three species is reported: Dadaya macrops Sars, 1901 first record of the genus for the state, Simocephalus serrulatus (Koch, 1841) and Simocephalus latirostris (Stingelin, 1906). The work presents brief descriptions and illustrations of the morphology of the studied species.